Heat distribution study on turbocharger turbine volute - Ardani, Mohd. Ibthisham (2012)
The aimed of this project is to evaluate turbine’s performance based on its actual condition. Holset H3B nozzles turbine geometry was used as simulation model. Turbine’s actual working condition was simulated using common computational fluid dynamics analysis software which is FLUENT. Initial analysis was done by onedimensional and two-dimensional analysis. Further investigation was done in threedimensional with heat loss via turbine volute by the mode of convection. All the simulation results were compared with established data in order to confirm its validity. The parameters studied are corrected mass flow, turbine’s efficiency at different heat cases, temperature distribution along turbine’s volute and difference in temperature between inner and outer wall temperature. Temperature difference within turbine’s volute is the major factor that deteriorates turbine’s efficiency. Since turbine wall is thin, small temperature difference will result to high heat loss.